Resilience Capacity of Pre-hospital Emergency Medical Service (EMS) Providers and the Future Agenda for Sustainable Development of A Resilient EMS System in Thailand - Alina Pant; Thunwadee Suksaroj; Piyapong Janmaimool; Orapin Laosee; Cheerawit Ratannapan (ACHSM, 2024)
In the current scenario, demand for emergency care is rising due to the shift in disease pattern all around the world, from growing burden of non-communicable diseases to the pre-existing communicable diseases. The principle aim of an emergency medical service (EMS) system is to prevent premature mortality, reduce pain and prevent long term disability. EMS workers serve on the front lines of emergency medical care, which is one of the most important components in an EMS system of any country. Since the latest pandemic has caused increased burn out and stress among the service providers with long term mental and physical effect which is yet to be researched in Thailand, and no study in particular have addressed to evaluate the resilience capacities of the front-line EMS workforce and identify components that influence their performance and response to emergencies. This study aims to measure the resilience capacity of pre-hospital EMS providers of Thailand along with providing recommendations to policy makers regarding EMS service provider future agendas and standard methods for proper workforce development in order to tackle future public health emergency situations. The respondents were EMTs, ENPs, paramedics, frontline rescuers working in the provinces as an EMS service provider under the ministry of public health (MOPH), National Institute of Emergency Medicine (NIEM), Thailand. Total 500 participated in the survey from 32 different provinces. Resilience capacity was divided into high, moderate and low; Components and factors were developed through literature review and grouping was done. With total 41 questions: Safety, Competencies, Wellness and Behavioral Health. Open ended questions reflected the perception and experiences of the EMS service providers regarding the strength and improvement areas of the EMS system in Thailand. The result from the survey shows that the EMS service providers have moderate resilience in terms of Behavioral Health which is related to their psychometric properties and main components to measure the resiliency scales. Similarly, in terms of Safety, Wellness and Competencies components the EMS services have shown moderate level of resilience capacity as a front-line worker in the emergency medical service system to prepare for the future public health emergencies. The findings of the research present the perception and opinions of various EMS providers working in different provinces of Thailand. This study explores the present status/situation of front-line workers of the EMS system in Thailand. The findings provide crucial recommendations to health policy makers for developing resilient EMS system and their workforce in Thailand focusing on pre-hospital care setting. This research suggests measurement tools and plans focusing on the EMS future agenda 2050.